STRUCTURAL, ELECTRONIC AND OPTICAL PROPERTIES OF BORON DOPED MONOLAYER GALLIUM ARSENIDE (GaAs) FOR OPTOELECTRONIC APPLICATION: A DFT STUDY - Manga, Anas; Itas, Yahaya Saadu; Dalhatu, Sadiq Abubakar; Aliyu, Aliyu Mohammed; Hassan, Asmau Muhammad; Bello, Mustapha; Abubakar, Abdullahi (FUDMA JOURNAL OF SCIENCES, 2025)
This work carried out investigations on the optoelectronic properties of two-dimensional gallium arsenide under some specific conditions. To achieve the aim and objectives of this research, detailed analysis of electronic, structural and optical absorptions is reported. The first principles calculations method within the density functional theory framework was used to study the structural, electronic and optical properties of boron (B) doped monolayer GaAs. The calculated lattice constants with PBE-GGA are 7.9871 Å, and 6.5861 Å for “a” and “c” respectively. The bandgap value of 0.43 eV was obtained for the undoped monolayer GaAs. When 6.25% of B is introduced into monolayer GaAs, the doping effects modified the band gap from 0.43 to 0.29 eV. Also, by introducing 12.50% of B to monolayer GaAs, the band gap value reduced to 0.12 eV. Our findings confirmed that boron doping narrows the energy band gap of monolayer GaAs semiconductor material. The results of optical absorption indicated that 6.25% B doped monolayer GaAs and 12.50% B monolayer GaAs have strong absorption behavior in the visible light frequency, which depicts its suitability for optoelectronic applications such as solar cells. The study revealed that band gap engineering using boron effectively allowed better control of electronic and optical properties of monolayer (2D) GaAs semiconductor, and enhances visible light absorption, making it superior to undoped GaAs for solar cells.
Keywords: Gallium arsenide; Optoelectronics; Monolayer; Visible light; DFT; Boron doping